All Days 2013
DOI: 10.2523/iptc-16946-ms
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Method to Mix Corrosion Inhibitor in Emulsified Acids

Abstract: Acid in oil emulsions stimulate carbonate formation of limestone and dolomite. These emulsions consist of internal inhibited acid phase and an external hydrocarbon phase mixed with an emulsifier. In this current technology, the corrosion inhibitor is dissolved in the acid phase and encapsulated by hydrocarbon in the outer phase. The facts that the corrosion inhibitor is inside the emulsion will retard it from dispersing on metal surface of the tubing to create a metal protective film. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The mixing process of four (10 cm-wide) shakes per second for 1 minute mixed all solid materials homogeneously. These materials were mixed with Safa (branded) water (Ca-Na-HCO 3 -C1-SO 4 ) [7]. The major ion concentrations and physical properties of the water (as indicated by the manufacturer) are illustrated in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…The mixing process of four (10 cm-wide) shakes per second for 1 minute mixed all solid materials homogeneously. These materials were mixed with Safa (branded) water (Ca-Na-HCO 3 -C1-SO 4 ) [7]. The major ion concentrations and physical properties of the water (as indicated by the manufacturer) are illustrated in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Water in oil emulsions provide better retardation due to the low diffusivity created by the oil phase around acid droplets, which allows for minimum acid volume contact with the rock–tubular surface. Thus, most research ,, ,,, , has adapted W/O emulsions due to their desirable retardation effect and corrosion inhibition in comparison to O/W emulsions, , as depicted in Figure .…”
Section: Emulsion and Its Typesmentioning
confidence: 99%
“…Beyond critical micelle concentration, droplet size does not decrease; however, in the case of pickering agents, this can lead to increased stability with a relatively lower amount than that used for surfactant. Moreover, macroemulsions are favored for matrix acidizing over microemulsions, which provide sufficient stability with ample acid volume. The use of a pickering emulsion and a hybrid emulsifier (combination pickering particles and surfactants or polymers) greatly minimizes the emulsifier concentration while forming a strong structural network, which provides enhanced stability. ,, …”
Section: Synthesis and Important Parameters For Ensuring Quality Emul...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the delayed nature of emulsified acid has attracted the attention of the oil and gas industry as it could decrease the reaction rate, reduce the contact between acid and well tabular and minimise corrosion issues that is related to well integrity, cost and above all issue associated with safety and environment. In carbonate matrix acidizing using emulsified acid, longer conductive flow paths or "wormholes" are induced, thus improving the permeability and productivity of the reservoir (Sabhapondit et al 2012;Al-Zahrani 2013;Fattah and Nasr-El-Din 2008). Experimental studies and real field application has indicated that emulsified acid can improve carbonate porosity and permeability while minimizing corrosion issues (Sayed et al 2013;Zakaria et al 2012;Navarrete et al 1998;Al-Anazi et al 1998).…”
Section: Introductionmentioning
confidence: 99%